How Can the United States and China Manage Their Ideological Differences and Competition? - Baogang HE (East Asian Policy, 2025)
Over the past two decades, ideological competition has sharply intensified geopolitical tensions between the United States and China, becoming a central factor in shaping their bilateral relations and strategic rivalry in the 21st century. Yet, a constructive framework for managing this ideological contestation remains undeveloped. This article explores the concept of strategic empathy as a critical framework for managing the ideological differences and competition between the United States and China.